Independent and Confluent Middle Mesial Root Canals in Mandibular First Molars: A Report of Four Cases. (25th June 2012) - Deepalakshmi, Mohanavelu; Karumaran, Chellasamy Savarimala; Miglani, Revathi; Indira, Rajamani
Abstract : Mandibular molars demonstrate considerable variations with respect to number of roots and root canals. The possibility of additional root canals should be considered even in teeth with a low frequency of abnormal root canal anatomy. This paper discusses the endodontic management of the rare anatomical complexity middle mesial canals in mandibular first molar and also serves to remind the clinicians that such anatomical variations should be taken into account during the endodontic treatment of the mandibular molars.